Unintended pregnancy and the factors among currently pregnant married youths in Western Oromia, Ethiopia: A mixed method. - Jaleta Merga (Public Library of Science (PLoS), 2021)
Background Unintended pregnancy is a global concern affecting both developed and developing countries. Some young women who had unintended pregnancies obtain an abortion while others carry their pregnancies to term, incurring the risk of morbidity and mortality higher than those for adult women. Despite the availability of highly effective methods of contraception, different studies in Ethiopia revealed that there is a high level of unintended pregnancy. Objective To assess the magnitude of unintended pregnancy and associated factors among currently pregnant married youths in Kiremu district. Methods A community-based cross-sectional study was conducted among currently pregnant married 15-24 years women. Multi-stage stratified sampling technique was used to select 434 study units. Ten kebeles were randomly selected and samples were selected from each of ten kebeles by simple random sampling using kebeles household identification numbers as the sampling frame. Quantitative data was entered with SPSS version 20 and crude and adjusted odds ratio together with their 95%CI were computed and interpreted accordingly. A p-value<0.05 was considered to declare a result as statistically significant in this study. In-depth interviews and transcripts of the recorded discussions were coded and analyzed thematically. The results were finally presented in texts, tables, and graphs. Result Unintended pregnancies among currently pregnant married young women in the study area were 31.1%. Educational status (AOR = 3.195,95%CI = 1.757,5.811),being Gov't employee (AOR = 0.039, 95% CI = 0.002,0.988), ever heard contraceptives(AOR = 0.260, 95%CI = 0.077, 0.876), ever used contraceptives (AOR = 0.348,95%CI = 0.168,0.717),discussion about contraceptives with husband(AOR = 0.027,95%CI = 0.015, 0.050),fear of side effect of contraceptives (AOR = 5.819,95% CI = 1.438,23.422), autonomy on health (AOR = 0.122,95%CI = 0.035,0.431), age at first marriage (AOR = 3.195, 95%CI = 1.757,5.811), age first pregnancy(AOR = 23.660,95%CI = 12.573,44.522), being visited by health care providers (AOR = 0.202,95%CI = 0.073,0.566) and average birth interval (AOR = 3.472,95%CI = 1.392,8.61) were the factors associated with unintended pregnancy. Conclusion and recommendation Significant proportion of women had an unintended pregnancy in the study area. Therefore, emphasis should be given to married youths especially on women empowerment, encouraging partner discussions, and providing appropriate counseling on contraceptive side effects by giving due attention to those marred at younger ages (<18 years).